2015
DOI: 10.1007/s11192-015-1580-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy evaluation of Scopus Author ID based on the largest funding database in Japan

Abstract: Teachers are most significant factor in education system. Teachers are playing very important role for the success of education system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 14 publications
0
44
0
Order By: Relevance
“…Although it has not been validated in the United States, a recent article showed the Scopus ® author identification search feature in Japan was 99% precise when compared to the largest funding database. 28 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has not been validated in the United States, a recent article showed the Scopus ® author identification search feature in Japan was 99% precise when compared to the largest funding database. 28 …”
Section: Methodsmentioning
confidence: 99%
“…Scopus has excellent author searching capabilities and was proven to be 99% in a recent Japanese study. 28 Fourth, we may not be able to identify post-residency publications in projects where the author changed the last name; to overcome this, we searched co-investigators to assess if there are co-authors on future papers. Many journals suggest incorporating ORCID (Open Researcher and Contributor ID) to submitted manuscripts.…”
Section: Limitationsmentioning
confidence: 99%
“…Scopus author IDs are automatically assigned by an author name disambiguation algorithm that prioritises precision (i.e., attempts to avoid conflating different researchers with the same name) (Moed & Plume, 2013). It accuracy seems to be high since a study of Japanese funded authors found it to have precision of 99% (99% of papers associated with an author ID were correctly assigned) and recall of 98% (98% of an author's papers were assigned to their ID) (Kawashima & Tomizawa, 2015). Duplicate IDs occurred in these lists when authors had multiple affiliations, reducing the total number of unique authors, for articles with large sets.…”
Section: Methodsmentioning
confidence: 99%
“…Both scholar and publication data were downloaded from Scopus , from 1999 to 2015, inclusive for the three identified universities. To avoid potential author name confusion, Scopus implements a reliable unique author ID (Kawashima & Tomizawa, ). For example, there are 31 Albert Einstein's in Scopus, and each one has a unique author ID.…”
Section: Methodsmentioning
confidence: 99%